2020
DOI: 10.3389/fgene.2020.00360
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Features and Population Genetic Structure of Dong, Yi, Han, and Chuanqing Human Populations in Southwest China Inferred From Insertion/Deletion Markers

Abstract: Guizhou province in southwest China has abundant genetic and cultural diversities, but the forensic features and genetic structure of Guizhou populations remain poorly understood due to the sparse sampling of present-day populations. Here, we present 30 insertion/deletion polymorphisms (InDels) data of 591 human individuals collected from four populations, Dong, Yi, Han, and Chuanqing residing in Guizhou. We calculated the forensic parameters of 30 InDel loci and found that this panel meets the efficiency of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The existing studies on the Chuanqing people showed that they were closely related to the Han and local ethnic groups in Guizhou such as the Miao in their social culture [20,21,53] or medical research [54]. Eleven medicinal plants were also recorded in the ChP, the QSG, and the Chuanqing people's medicine simultaneously, suggesting that the diseases treated with medicinal plants by the Chuanqing people were similar to those found among the ChP and the QSG.…”
Section: Comparison With Chp the Qsg And Southeast Asian Medicinesmentioning
confidence: 93%
See 1 more Smart Citation
“…The existing studies on the Chuanqing people showed that they were closely related to the Han and local ethnic groups in Guizhou such as the Miao in their social culture [20,21,53] or medical research [54]. Eleven medicinal plants were also recorded in the ChP, the QSG, and the Chuanqing people's medicine simultaneously, suggesting that the diseases treated with medicinal plants by the Chuanqing people were similar to those found among the ChP and the QSG.…”
Section: Comparison With Chp the Qsg And Southeast Asian Medicinesmentioning
confidence: 93%
“…They live mainly in Nayong County and Zhijin County of Guizhou Province [19]. According to the genetic relationship, the Chuanqing people are similar to the south Han, Miao, She, and Tujia ethnicities [20,21]; it is a community with multiple ethnic groups. Every year, on the fifth day of the fifth month of the Chinese lunar calendar, the Chuanqing people in Nayong County prepare a grand herbal market at the DBF.…”
Section: Introductionmentioning
confidence: 99%
“…The overall language landscape of the Chinese population is dominated by more than 10 mainly language families (including Tai-Kadai, Hmong-Mien, Tungusic, Indo-European, Austroasiatic, Austronesian, Turkic, Mongolic, Koranic, and Sino-Tibetan) ( Cavalli-Sforza, 1998 ). However, Guizhou populations are reported to be dominated by the Tai-Kadai, Hmong-Mien, and Sino-Tibetan-speaking families ( Chen et al, 2018 ; Liu et al, 2020 ). A large number of population genetic researches have been conducted and primarily focused on the forensic polymorphism and genetic structure of the Guizhou Hans via STRs included in the AGCU X19 amplification system or InDels included the Investigator DIPplex kit ( Chen et al, 2018 ; He et al, 2019 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies on the Chuanqing showed that it was closely related to the Han and the local ethnic groups in Guizhou such as the Miao in their social culture [20,21,54] or medical research [55]. Eleven medicinal plants were also recorded in the ChP, the QSG and the Chuanqing's medicine coinstantaneously.…”
Section: Discussionmentioning
confidence: 99%
“…They live mainly in Nayong County and Zhijin County of Guizhou Province [19]. According to the genetic relationship and formation, the Chuanqing is similar to the south Han, Miao, She and Tujia [20,21], it is a community with multiple ethnic groups. On the fth day of the fth month of the Chinese lunar calendar every year, the Chuanqing in Nayong County prepares a grand herbal market at the DBF.…”
Section: Introductionmentioning
confidence: 99%